2021
DOI: 10.1155/2021/6680626
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multiple Surface Ocean Wind Products with Buoy Data over Blue Amazon (Brazilian Continental Margin)

Abstract: Remote sensing data for space-time characterization of wind fields in extensive oceanic areas have been shown to be increasingly useful. Orbital sensors, such as radar scatterometers, provide data on ocean surface wind speed and direction with spatial and temporal resolutions suitable for multiple applications and air-sea studies. Even considering the relevant role of orbital scatterometers to estimate ocean surface wind vectors on a regional and global scale, the products must be validated regionally. Six dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 69 publications
(94 reference statements)
1
7
0
1
Order By: Relevance
“…Overall, excluding Silleiro and Cadiz, the models-based data show smaller deviations from what is observed. It is observed that for some locations, the highest errors are obtained for lower velocities, which is in accordance with the overall idea that the weaker the winds are, the higher errors are obtained due to the greater variance of wind direction and higher STDs [10,45]. However, the three PdE stations on the northern coast present high differences concerning observations for higher velocity bins.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Overall, excluding Silleiro and Cadiz, the models-based data show smaller deviations from what is observed. It is observed that for some locations, the highest errors are obtained for lower velocities, which is in accordance with the overall idea that the weaker the winds are, the higher errors are obtained due to the greater variance of wind direction and higher STDs [10,45]. However, the three PdE stations on the northern coast present high differences concerning observations for higher velocity bins.…”
Section: Discussionsupporting
confidence: 82%
“…It is observed that the mean OSW is underestimated for most stations by Sentinel-1, ERA5 and WRF and overestimated by ASCAT. The mean velocity underestimation by reanalysis as ERA5 was already stated by [45][46][47] over the Brazilian Continental Margin and coastal regions of Mexico, reporting that the reanalysis tends to underestimate the wind speeds at a majority of the sites. In the WRF configuration used in this study, the mean wind velocity is underestimated, however [9], showed a tendency of a WRF configuration to overestimate the wind speed.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…According to the suggestion of relevant literature [24], the data used in this paper mainly include: 1) the real-time observation data of Zhejiang coastal wind towers, with a time resolution of 10min, and the observation data and location information are shown in Table 1 and Figure 1; 2) The reanalysis data of ERA-Interim is published by ECMWF, including the sea surface 10 m wind speed, sea surface temperature, sea surface pressure. The spatial resolution is 0.125 °× 0.125 °, the spatial range is 120 °E-125 °E, 27.125 °N-30.75 °N.…”
Section: Data Selection and Calculation Methodsmentioning
confidence: 99%
“…Recent studies focused on the evaluation of surface winds along coastal areas over the South Atlantic Ocean. Paiva et al ., 2021 evaluated wind speed and direction from reanalysis, a satellite‐based gridded calibrated dataset and scatterometer products to moored buoys in the Brazilian margin. Their results indicate that scatterometers provide a better fit to in situ data, followed by the calibrated satellite data and the recent reanalysis product from European Centre for Medium‐Range Weather Forecasts (ECMWF), ERA5.…”
Section: Introductionmentioning
confidence: 99%